Radioaktives Cäsium im Fisch der Barentssee weiterhin abnehmend - Kellermann, Hans-Jürgen (1997)
A decrease of 137Cs concentration in cod flesh from Barents Sea is shown by six years random sampling. This reduction runs parallel to reduced emissions from the nuclear fuel reprocessing plant Sellafield (Great Britain). It must be emphasized that even the highest values from 1992 are lower than comparable ones from the North Sea and from the Baltic. Although there is no increase of the radiation dose on people by consuming these fishes further monitoring should not be stopped. Potential risk arises from radioactive wastes of the russian nuclear navy in their coastal area. Obviously a safe storage seams almost too expensive. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.